Higher-Order Splitting Method for Elastic Wave Propagation - Jürgen Geiser (International Journal of Mathematics and Mathematical Sciences)
Motivated by seismological problems, we have studied a fourth-order split scheme for the elastic wave equation. We split in the spatial directions and obtain locally one-dimensional systems to be solved. We have analyzed the new scheme and obtained results showing consistency and stability. We have used the split scheme to solve problems in two and three dimensions. We have also looked at the influence of singular forcing terms on the convergence properties of the scheme.